2007
DOI: 10.11130/jei.2007.22.4.852
|View full text |Cite
|
Sign up to set email alerts
|

The Free Trade Agreement Between the United States and Morocco: The Importance of a Gradual and Assymetric Agreement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…These results are similar with those of Jallab, Abdelkmalki and René Sandretto (2007) on the impact of FTA between the United States and Morocco. They have found that, the agreement led to a total welfare gain by Moroccan consumers because they had access to goods at lower prices.…”
Section: Simulation Results and Discussionsupporting
confidence: 91%
“…These results are similar with those of Jallab, Abdelkmalki and René Sandretto (2007) on the impact of FTA between the United States and Morocco. They have found that, the agreement led to a total welfare gain by Moroccan consumers because they had access to goods at lower prices.…”
Section: Simulation Results and Discussionsupporting
confidence: 91%
“…A similar study conducted in the United States by Abdelmalki et al (2007) simulated the effect of the free trade agreement between the United States and Morocco with the WITS-SMART model. The output revealed that the bilateral trade agreement between the two nations significantly impacted their trading relationships.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…We base this section on Laird and Yeats (1986) and related papers that apply SMART (James & Olarreaga, 2005;Khorana et al, 2009;Makochekanwa, 2014;Sadni Jallab et al, 2007) but adjust the notation to better match the standard used in the input-output analysis that follows. Let us start by defining the main variables in our trade analysis: TL iSR -Trade loss effect on commodity i imported from country R into country S. TD iSR -Trade diversion effect on commodity i imported from R into country S. M iSR -Imports of commodity i to country S from exporting country R. M iSRW -Imports of commodity i by S from the rest of the world.…”
Section: Technical Notation For the Trade Analysismentioning
confidence: 99%